APPLICATION OF SOFT OPEN POINT FOR OPTIMIZATION OF ELECTRICITY LOSSES IN DISTRIBUTION NETWORKS - LOBODA, YURIY; SLOBODIAN, RUSLAN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The increase in consumer load and the introduction of renewable energy sources lead to the need for reconstruction or modernization of distribution electrical networks. In global practice, unified devices based on modern power electronics are increasingly being used. This equipment is expensive, but in recent years in Ukraine the cost of electricity has increased significantly, which ensures the technical and economic efficiency of installing these devices. One such device is the Soft Open Point (SOP), which is used in distribution networks to reduce electrical energy consumption by compensating reactive power and redistributing active power in adjacent feeders. The article analyzes the dependence of electricity consumption on the mode of operation of the SOP and determines the regularities of optimizing the mode of its operation according to the criterion of minimum electricity consumption. A calculation was made based on real data of F-33 and F-45 of Khmelnytskyi REM using a typical daily load schedule of household consumers, which showed a reduction of active electricity losses by 14.2%. We also offer a control strategy based on balanced real and apparent component voltages between nodes of the installed SOP. The results of the control strategy were verified according to the steady-state calculation of the network with fixed loads. Then, before analyzing the results, the reduction of annual electricity costs due to the placement of the SOP was calculated, and its useful life was calculated, which is 8 years, and when the load is tripled, the useful life decreases to 2.8 years. The obtained results substantiate the possibility of abandoning the SOP, in order to optimize electricity losses, in the distribution power networks of Ukraine.
Keywords: Soft Open Points; electrical networks; power losses